Renewable hydrogen economy outlook in Africa - Mukelabai, Mulako Dean; Wijayantha, Upul K. G.; Blanchard, Richard E. (Elsevier, 2022)
Hydrogen presents an opportunity for Africa to not only decarbonise its own energy use and enable clean energy access for all, but also to export renewable energy. This paper developed a framework for assessing renewable resources for hydrogen production and provides a new critical analysis as to how and what role hydrogen can play in the complex African energy landscape. The regional solar, wind, CSP, and bio hydrogen potential ranges from 366 to 1311 Gt/year, 162 to 1782 Gt/year, 463 to 2738 Gt/year, and 0.03 to 0.06 Gt/year respectively. The water availability and sensitivity results showed that the water shortages in some countries can be abated by importing water from regions with high renewable water resources. A techno-economic comparative analysis indicated that a high voltage direct current (HVDC) system presents the most cost-effective transportation system with overall costs per kg hydrogen of 0.038 $/kg, followed by water pipeline with 0.084 $/kg, seawater desalination 0.1 $/kg, liquified hydrogen tank truck 0.12 $/kg, compressed hydrogen pipeline 0.16 $/kg, liquefied ammonia pipeline 0.38 $/kg, liquefied ammonia tank truck 0.60 $/kg, and compressed hydrogen tank truck with 0.77 $/kg. The results quantified the significance of economies of scale due to cost effectiveness of systems such as compressed hydrogen pipeline and liquefied hydrogen tank truck systems when hydrogen production is scaled up. Decentralization is favorable under some constraints, e.g., compressed hydrogen and liquefied ammonia tank truck systems will be more cost effective below 800 km and 1400 km due to lower investment and operation costs.
Keywords: Hydrogen production; Centralization vs decentralization; Large-scale vs small scale; Hydrogen utilisation; Hydrogen storage; transportation and distribution; Water-energy-food nexus